2014
DOI: 10.1038/bjc.2014.383
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 promotes tumour growth and metastasis in colorectal cancer through binding to SFPQ and releasing oncogene PTBP2 from SFPQ/PTBP2 complex

Abstract: Background:Metastasis associated with lung adenocarcinoma transcript-1 (MALAT1) is a functional long non-coding RNA (lncRNA), which is highly expressed in several tumours, including colorectal cancer (CRC). Its biological function and mechanism in the prognosis of human CRC is still largely under investigation.Methods:This study aimed to investigate the new effect mechanism of MALAT1 on the proliferation and migration of CRC cells in vitro and in vivo, and detect the expression of MALAT1, SFPQ (also known as P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
267
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(280 citation statements)
references
References 39 publications
12
267
0
1
Order By: Relevance
“…Mutations have also been identified in this fragment 185 . The higher expression of MALAT-1 is correlated with cell proliferation, migration, and invasion and observed in metastatic tumors 186 . MALAT-1 promotes tumor metastasis in nude mice by inhibiting the polypyrimidine tract binding protein 2 (PTBP2)/splicing factor proline/glutamine-rich (SFPQ) complex and releasing the oncogene PTBP2.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript-1 (Malamentioning
confidence: 99%
“…Mutations have also been identified in this fragment 185 . The higher expression of MALAT-1 is correlated with cell proliferation, migration, and invasion and observed in metastatic tumors 186 . MALAT-1 promotes tumor metastasis in nude mice by inhibiting the polypyrimidine tract binding protein 2 (PTBP2)/splicing factor proline/glutamine-rich (SFPQ) complex and releasing the oncogene PTBP2.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript-1 (Malamentioning
confidence: 99%
“…Recently, aberrantly expressed lncRNAs have been found related with CRC. As examples, lncRNAs such as CCAT1 [24][25], CCAT2 [26], HOTAIR [27] and MALAT1 [28] are increased in CRC tissues compared to NATs and have been identified as oncogenes. The lncRNAs can regulate the expression of their target genes, activate some signaling pathways, and promote cell proliferation, metastasis, and tumor recurrence [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that the expression of MALAT-1 was higher in human CRC tissues than adjacent normal tissues (54). MALAT-1 upregulation has been demonstrated in CRC tumors.…”
Section: Potential Clinical Applications Of Malat-1mentioning
confidence: 97%
“…Additionally, MALAT-1 may competitively bind to SFPQ to release SFPQ from the SFPQ/polypyrimidine tract binding protein 2 (PTBP2) complex in CRC LoVo cells. SFPQs, not PTBP2 proteins, are critical in the regulatory effect (54). In esophageal squamous cell carcinoma, MALAT-1 is suppressed by sex determining region Y (SRY)-box 17 via SRY binding-mediated transcriptional regulation (55).…”
Section: Molecular Targets Of Malat-1mentioning
confidence: 99%